Association between COX-2 gene polymorphisms and risk of hepatocellular carcinoma development: a meta-analysis. Issue 10 (5th October 2015) - Lu, Si-Cong; Zhong, Jian-Hong; Tan, Jun-Tao; Tang, Hua-Lin; Liu, Xiao-Guang; Xiang, Bang-De; Li, Le-Qun; Peng, Tao
Abstract : Objective: To investigate the association between cyclo-oxygenase-2 (COX-2) polymorphism and the risk of hepatocellular carcinoma (HCC) development. Design: Systematic review and meta-analysis of COX-2 polymorphism and risk of HCC development among people with or without HCC. Data sources: EMBASE, PubMed, Public Library of Science, SCOPUS, Web of Knowledge and Chinese National Knowledge Infrastructure were searched for all clinical and experimental case–control studies of COX-2 polymorphism and HCC risk. Studies published up to March 2015 were included. Review method: Ten studies were included for data extraction, which were mainly from Asian countries. Results: 2538 people with HCC and 3714 without HCC were found to satisfy the inclusion criteria and included in the review. The associations of specific genotypes in the eight polymorphic variants of COX-2 and the risk of HCC development were analysed. GG genotype at the A-1195G polymorphism may be associated with a reduced risk of HCC development: the OR across all studies was 0.87 (95% CI 0.75 to 1.02) for the G allele versus the A allele, 0.72 (0.53 to 0.97) for GG versus AA, 0.72 (0.57 to 0.92) for GG versus GA+AA and 1.05 (0.77 to 1.44) for AA versus GA+GG. Similar results were found when the meta-analysis was repeated separately for the Chinese subgroup. However, more reliable data are needed to demonstrate associations between variants in G-765C, T+8473C, A-1290G, G-899C and introns 1, 5 and 6 polymorphisms and the risk of HCC development. Conclusions: Only the COX-2 A-1195G gene polymorphism may be associated with a decreased risk of HCC development. These conclusions should be verified in further studies.